Clinico-pathological correlation and outcome in patients with mesangioproliferative glomerulonephritis in Cape Town: A single centre study - Barday, Zibya (Division of Nephrology and Hypertension, 2019)
Background Glomerulonephritis is a major cause of end-stage kidney disease (ESRD) in Africa. There is scanty data on the clinico-pathological characteristics and outcome of the mesangioproliferative glomerulonephritides in Africa, despite the non-IgA subtype being reported as a common cause of nephrotic syndrome. This study will assess the outcome of patients with biopsy proven mesangioproliferative glomerulonephritis (MesPGN) from a single centre in Cape Town, South Africa. Methods The study is designed as 10-year retrospective analysis of patients with biopsy proven MesPGN. The MesPGN patterns were divided into non-IgA MesPGN and IgA nephropathy (IgAN), depending on the predominant type of immune deposit. Univariate cox regression analysis was used to determine factors associated with ESRD. Results Data of 109 patients with renal biopsy-proven MesPGN were included for the period between 2005-2014. The mean age at biopsy was 33.8 ±14.9 years, 53.2% were males, and 39.4% were black Africans. Clinically, 58.7% presented with nephrotic syndrome. On histology 79.8% had non-IgA MesPGN, and 20.2% had IgAN. Compared to the non-IgA group, most patients with IgAN were not treated with immunosuppression (72.7% vs. 40.2%; p=0.006). At the last visit, 10.1% reached ESRD (40.9% vs. 2.3%; p<0.0001) and 30.2% achieved complete remission (9.1% vs. 35.7%; p=0.015) for IgAN and non-IgA MesPGN respectively. The 5-year renal survival for IgAN and non-IgA MesPGN respectively, were: 63.3% vs. 97.6%, log rank p=0.001. Overall, hypertension (p=0.019), not receiving immunosuppression (p=0.046) and having IgAN (p=0.007) were independent predictors of progression to ESRD. Conclusion There is a significantly higher ESRD-free survival of patients with biopsy proven non-IgA MesPGN than IgAN. Whether this is related to the limited use of immunosuppressive therapy in IgAN patients or represents a true nature of the disease still requires further research.